2023
DOI: 10.1186/s12964-023-01173-6
|View full text |Cite
|
Sign up to set email alerts
|

P38-DAPK1 axis regulated LC3-associated phagocytosis (LAP) of microglia in an in vitro subarachnoid hemorrhage model

Abstract: Background The phagocytosis and homeostasis of microglia play an important role in promoting blood clearance and improving prognosis after subarachnoid hemorrhage (SAH). LC3-assocaited phagocytosis (LAP) contributes to the microglial phagocytosis and homeostasis via autophagy-related components. With RNA-seq sequencing, we found potential signal pathways and genes which were important for the LAP of microglia. Methods We used an in vitro model of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Interestingly, the LAP is an essential part of microglial phagocytosis in the brain. Chen et al demonstrated that DAPK1 is also involved in the regulation of LAP in the microglia using an in vitro subarachnoid hemorrhage model by exposing microglial cells to oxyhemoglobin [ 200 ]. Oxyhemoglobin suppresses microglial LAP by upregulating p38 and downregulating DAPK1, further resulting in a reduction of cellular Beclin1 expression [ 200 ].…”
Section: The Role Of Dapk1 In Alzheimer’s Core Pathologiesmentioning
confidence: 99%
“…Interestingly, the LAP is an essential part of microglial phagocytosis in the brain. Chen et al demonstrated that DAPK1 is also involved in the regulation of LAP in the microglia using an in vitro subarachnoid hemorrhage model by exposing microglial cells to oxyhemoglobin [ 200 ]. Oxyhemoglobin suppresses microglial LAP by upregulating p38 and downregulating DAPK1, further resulting in a reduction of cellular Beclin1 expression [ 200 ].…”
Section: The Role Of Dapk1 In Alzheimer’s Core Pathologiesmentioning
confidence: 99%